[Sub]vidas secas nos retratos dos agricultores do Projeto Bebedouro no seminário de Petrolina (PE) - Nathália de Fátima Joaquim (2014)
The objective of this study was to analyse the ordinary management developed by farmers in Projeto de Irrigação Bebedouro, a pioneer in the São Francisco Valley. Therefore, it was done ethnographic research combined with the methods of oral history. With the development of research, it was observed that, to understand the situation of the Projeto Bebedouro and hence the survival tactics undertaken by farmers, called settlers, it was necessary to explore broader concepts such as land configuration and drought industry locally. Thus, it was possible to observe that the ordinary management adopted by the settlers is a reflection of land conditions to which they are subjected, and also by not overcoming the drought industry and its developments as the Coronelismo and vote of muzzle. The Project was launched in 1968 and had 16 lots. The 16 settlers who assumed these lots are called pioneers and was here from the stories of their lives that this work was built. At the inauguration, was implanted in imposing manner, a cooperative to assist the settlers in the processes of production and marketing, through ordinary management settlers / associated with failed and contracted high debts. The purpose of government agencies such as the Companhia de Desenvolvimento do Vale do São Francisco (CODEVASF) was to implement an agrobusiness complex in the region, which brought a cyclical nature to the Projeto Bebedouro, in other words, from time to time, the settlers cultivate certain products. Therefore, large companies were attracted to the region and settlers were encouraged to plant tomatoes. The agrobusiness complex around the tomato did not work then the settlers invested in fruit growing. This was already giving air that was at the end of cycle, thus began the production of basic seed marketed through contracts with Embrapa Produtos e Mercados. This was the cycle that began in Projeto Bebedouro during this research. So for [sub]live in the Projeto Bebedouro, the settlers adopted tactics such as the production of food for household consumption through the production of basic seed and fruit that are sold to middlemen or through such contracts, respectively. Given these practices, it can be stated that the ordinary management is an organizational form adopted by settlers Projeto Bebedouro as a tactic of survival and endurance in the midst of everyday life that oppresses them.